Effects of short-term −12° head-down tilt on cognitive performance. (October 2020) - Dayal, D.; Jesudasen, S.; Scott, R.; Stevens, B.; Hazel, R.; Nasrini, J.; Donoviel, D.; Basner, M.
Abstract: Background: Microgravity-induced fluid shifts and the resulting changes in cerebral hemodynamics may be linked to cognitive performance alterations in spaceflight. Head-down tilt (HDT) bed rest serves as a well-validated spaceflight analog for microgravity-induced cephalic fluid shifts. This study examined the effects of short-term (t < 4 h) changes in body position (supine or −12° HDT) relative to a 45° upright position on cognitive performance. Methods: In this within-subject cross-over study, ten male subjects without significant medical comorbidities (mean ± standard deviation [SD] age: 34 years ±3, weight: 81 kg ± 11, height: 1.77 m ± 0.06, body mass index: 26 kg/m 2 ± 3) performed the Cognition test battery on an iPad at baseline (45° upright), after 1, 2, 3, and 4 h in the −12° HDT or supine position, and after 30-minute recovery in 45° upright position. The order of conditions (−12° HDT or supine) was randomized, with >1 week washout between test days. Results: Mixed model analyses of z-transformed Cognition test scores indicate a small (0.21–0.25 SD) decrease in accuracy that did not survive adjustment for multiple testing and no change in speed (0.00–0.12 SD) across cognitive domains in the supine and −12° HDT position relative to upright. A true decrease in speed may have been masked by practice effects, as speed was found to increase by 0.06 SD per test bout in condition (95% confidence interval 0.03; 0.10). Performance differences between −12° HDT and supine positions across cognitive domains were less than small (<0.2 SD) according to conventional standards. Discussion: This study on short-term positional changes on cognitive performance suggests that performing Cognition in the supine or −12° HDT position on a tablet is associated with small decreases in accuracy and, if practice effects are taken into account, potentially also speed, but with no relevant differences between positions. These findings help interpret bed rest studies that use the new −12° HDT paradigm. Highlights: First study to examine 4 h in −12° head-down tilt on cognitive performance. Effect sizes of differences between three body positions small or not detectable. Findings aid in interpretation of head-down-tilt bed rest studies. Findings aid in interpretation of cognitive changes in simulation of microgravity.